Acoustic tweezers based on circular, slanted-finger interdigital transducers for dynamic manipulation of micro-objects. Issue 5 (3rd February 2020) - Kang, Putong; Tian, Zhenhua; Yang, Shujie; Yu, Wenzhuo; Zhu, Haodong; Bachman, Hunter; Zhao, Shuaiguo; Zhang, Peiran; Wang, Zeyu; Zhong, Ruoyu; Huang, Tony Jun
Abstract : Acoustic tweezers based on circular, slanted-finger interdigital transducers enable programmable, dynamic, biocompatible manipulation of micro-objects. Abstract : Acoustic tweezing technologies are gaining significant attention from the scientific communities due to their versatility and biocompatibility. This study presents acoustic tweezers based on circular, slanted-finger interdigital transducers (CSFITs), which can steer the propagation direction of surface acoustic waves (SAWs) by tuning the excitation frequency. The CSFITs based acoustic tweezers enable dynamic and reconfigurable manipulation of micro-objects using multi-tone excitation signals. Compared to traditional interdigital transducers that generate and control SAWs along one axis, the CSFITs allow for simultaneously generating and independently controlling SAWs propagating along multiple axes by changing the frequency composition and the phase information in a multi-tone excitation signal. Moreover, the CSFITs based acoustic tweezers can be used for patterning cells/particles in various distributions and translating them along complex paths. We believe that our design is valuable for cellular-scale biological applications, in which on-chip, contactless, biocompatible handling of bioparticles is needed.